Trends & Future Directions of Digital Health Technology Implementation in India for Strengthening the Health Care Delivery in the Present Era - Chowdhury, Anirban Roy (Digital Repository of Theses, 2025)
Digital health technologies have emerged as a transformative force in addressing India’s healthcare challenges, including accessibility, affordability, and quality of care. This dissertation explores the digital health readiness of healthcare professionals, patients, and key stakeholders, highlighting both opportunities and barriers to the adoption of these technologies. The study focuses on India’s diverse demographic, socio-economic, and geographic landscape to provide a comprehensive understanding of the digital divide, the adoption of digital health tools, and the impact of government initiatives. The research employs a mixed-methods approach, combining an extensive review of literature with a survey of healthcare professionals and the general population. The findings reveal significant optimism about digital health’s potential, with 73.8% of healthcare professionals expressing confidence in using digital tools and 48.4% agreeing that these technologies improve patient outcomes. However, challenges persist, including inadequate training (61.1%), lack of system integration (57.1%), limited awareness (64.3%), and digital literacy gaps (58.7%) among patients, particularly in rural areas. Vulnerable groups, such as geriatric patients and lower socio-economic communities, face disproportionate barriers to accessing digital health services. Government initiatives like the Ayushman Bharat Digital Mission (ABDM) and the National Digital Health Blueprint (NDHB) have laid the groundwork for a unified digital health ecosystem. These initiatives promote interoperability, enhance data security, and foster patient empowerment. However, gaps in infrastructure, affordability, and enforcement of privacy frameworks hinder widespread adoption. The study emphasizes the need for targeted interventions, including national digital literacy campaigns, subsidized access to digital tools, enhanced cybersecurity measures, and incentives for healthcare providers to adopt digital platforms. Future research should focus on long-term impact assessments, cultural factors influencing adoption, and the integration of traditional and digital healthcare models. In conclusion, while digital health technologies offer immense potential to revolutionize healthcare in India, addressing systemic barriers and fostering a collaborative, multi-stakeholder approach is critical. This research provides actionable insights and a roadmap for policymakers, technology developers, and healthcare providers to create an equitable, efficient, and patient-centric healthcare ecosystem.